2022
DOI: 10.1101/2022.03.11.484020
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MUC5B mobilizes and MUC5AC spatially aligns mucociliary transport on human airway epithelium

Abstract: Airway mucus acts as a protective barrier and vehicle for clearance of pathogens, providing the lungs with a defense mechanism called mucociliary clearance (MCC). Airway mucus is composed of two mucins, mucin 5B (MUC5B) and 5AC (MUC5AC) that form a hydrogel that enables functional clearance in health. However, abnormalities in mucin expression, specifically increases in MUC5AC is observed in chronic respiratory diseases and leading to defective MCC. Our current understanding of MCC impairment focuses on mucin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…These cultures are of particular benefit in experiments that demand large quantities of HAE cultures/replicates beyond those available from primary cell sources. Additionally, the extended passage capacity of BCi-NS1.1 cells enables sophisticated genetic engineering techniques (with corresponding antibiotic selection) for mechanistic studies of airway cell function and disease 26 that can be technically challenging or infeasible in primary cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These cultures are of particular benefit in experiments that demand large quantities of HAE cultures/replicates beyond those available from primary cell sources. Additionally, the extended passage capacity of BCi-NS1.1 cells enables sophisticated genetic engineering techniques (with corresponding antibiotic selection) for mechanistic studies of airway cell function and disease 26 that can be technically challenging or infeasible in primary cells.…”
Section: Discussionmentioning
confidence: 99%
“…BCi.NS1.1 is an airway basal cell line isolated from a healthy, non-smoking male donor, engineered to express hTERT, which extends passage capacity to up to 40 times without losing differentiation potential, as compared to a limit of only 3-4 passages with untransduced primary cells 5 . Previous studies have demonstrated that BCi-NS1.1 differentiates into HAE cultures with similar morphology and cell type composition to primary HAE cultures, and this system has been leveraged for a variety of applications 5,2426 . However, the effects of hTERT expression on rare airway cell composition and associated gene expression programs in differentiated HAE cultures have been incompletely characterized, and any potential functional consequences for infection models with respiratory pathogens have not been directly explored.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation